Black queer flesh : rejecting subjectivity in the African American novel - Henry, Alvin J. (Minneapolis, MN : University of Minnesota Press, 2020)
"A groundbreaking examination of how twentieth-century African American writers use queer characters to challenge and ultimately reject subjectivity"--
Introduction: Toppling Subjectivity -- Passing into Racial Anxiety -- Nella Larsen and the Emergence of Black Queer Flesh -- Queer Underworlds in Ralph Ellison -- Social Protest and the Aesthetics of Flesh in Richard Wright -- Toward a Black Queer Utopia.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 07, 2021).
JSTOR
Keywords: African American gay people in literature; American fiction -- African American authors; American fiction -- 20th century; Homosexuality in literature; African Americans in literature; Self in literature; Personnes homosexuelles noires américaines dans la littérature.; Roman américain -- Auteurs noirs américains.; Roman américain -- 20e siècle.; Homosexualité dans la littérature.; Noirs américains dans la littérature.; Moi (Psychologie) dans la littérature.; LITERARY CRITICISM / American / African American